Pemphigus Foliaceus—Repeated Treatment With Rituximab 7 Years After Initial Response: A Case Report - Kraft, Magdalena; Worm, Margitta (Frontiers in Medicine, 2018)
Pemphigus foliaceus is an autoimmune skin disease mediated by autoantibodies directed against desmoglein-1 located in the upper epidermal layer. Rituximab, a monoclonal anit-CD20 antibody depleting b-cells, offers an effective treatment possibility for therapy-resistant pemphigus foliaceus. Here, we present the case of 55-year-old man who did not respond sufficiently to conventional treatment with prednisolone, azathioprine, and cyclophosphamide, but underwent almost complete remission after rituximab treatment. The patient relapsed 7 years later, and a repeated course of rituximab infusions led to a positive response.